Optimization of Low-Dose Pediatric Chest CT Examination: Pediatric Phantom Study: Dafa Miftahuddin, Audiena Gelung Prayitno, Aditya Prayugo Hariyanto, Djuli Pontjowijono, Endarko Endarko - Dafa Miftahuddin Dafa Miftahuddin; Audiena Gelung Prayitno Audiena Gelung Prayitno; Aditya Prayugo Hariyanto Aditya Prayugo Hariyanto; Djuli Pontjowijono Djuli Pontjowijono; Endarko Endarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
This study uses a Pediatric Thoracic phantom developed in-house to optimize low-dose pediatric chest CT examinations based on organ-specific dose and image quality. Four low-dose protocols, low kV and low mA, reconstructed using Filtered Back Projection (FBP) and iterative reconstruction (IR) algorithms, were investigated. Lung, heart, and spinal cord doses were measured using calibrated Gafchromic LD-V1 Film. Evaluation of image spatial resolution and noise are considered. The CTDIvol results underestimate organ-specific doses. Low kV exposed an average dose of 29.55% less than low mA. No significant differences existed in the MTF curves of standard, low mA, or low kV doses. The peak NPS for low kV is significantly higher than for low mA. The combination of low kV and FBP produces images with better high spatial resolution. Meanwhile, combining low mA with an IR algorithm effectively reduces image noise so that low-contrast object detection improves.